Special events and attractions in cultural tourism: Successful practices and new trends - Alexieva, Sonya (Leadership, Society, Strategic Visions, 2021)
Investment and changing attitudes towards cultural tourism which has grown increasingly high in demand among the various types of special interest tourism make of it a popular choice among Bulgarian and international tourists. In the era of social networks, the possibility for on-line exchange of comments and opinions has changed forever the way cultural tourism is managed and communicated. This type of special interest tourism requires a particular attention to special events, attractions, and modern animation. This paper deals with how our country’s chances as a promising cultural tourism destination can be enhanced at the background of the new trends in event management. It analyzes some good practices related to notorious special events and attractions and making many successful destinations recognizable.